Identification of the dominant gammaproteobacteria community in the anchialine environment in Lamao Caves, Dingalan, Aurora, Philippines - De Vera, Clarisse Gale L. Eustaquio, Arsenio Gideon M. Paguio, Naomi Grace C. 4 0 16; 5
ABSTRACT: Anchialine is a tidally-influenced subterranean estuary situated within karst and volcanic terrains. This environment is characterized by its unique characteristics and extreme conditions, which make it able to promote the existence of novel organisms. Anchialine environments are widely distributed across the globe. Despite this, there are few to communities. no local studies regarding anchialine ecosystems and microbial The study aims to characterize the anchialine environment and determine which gammaproteobacteria community is dominant and present in the anchialine environment in the Lamao Caves in Dingalan, Aurora. The sampling site was plotted at the entrance of the cave during the sampling, which is the farthest accessible point. Two (2) depth levels were set up with respect to the halocline. In total, six 6) water samples were collected and sent to a laboratory for processing. It was inoculated in Nutrient Agar (NA) to promote microbial growth and MacConkey Agar to inhibit other microbial growth except gammaproteobacteria species. Four (4) bacterial colonies were selected for genetic sequencing. NCBI Blast and MEGA software were utilized for the identification of the samples. Results showed that there gram-negative bacteria species (Acinetobacter seohaensis). Additionally, description of the specific anchialine environment from which these microbial species were collected, was described in this research study. The anchialine environment of the Lamao Caves exhibits characteristics such as neutral pH, low temperature, below-average salinity, and diminished dissolved oxygen levels. Notably, the physicochemical parameters exhibit a strong negative association with microbial growth. This research study contributed significant insights into the microbial community of an anchialine environment in the Philippines. In the local context, this study is the first of its kind to provide data on the assemblages of microorganisms in anchialine caves. Further research on this complex environment is crucial for comprehensive ecological assessments and conservation efforts. Keywords: Anchialine, Halocline, Gammaproteobacteria, Microbial assemblages
Undergraduate Thesis: (BS in Biology major in Ecology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2